Investigation on sub-23 nm particles and their volatile organic fraction (VOF) in PFI/DI spark ignition engine fueled with gasoline, ethanol and a 30 %v/v ethanol blend. (March 2021) - Di Iorio, Silvana; Catapano, Francesco; Magno, Agnese; Sementa, Paolo; Vaglieco, Bianca Maria
Abstract: Growing interest of the European Union to introduce new emission regulations seeking to lower the particle cut-off size down to the current limit set at 23 nm, has made crucial to achieve an extensive comprehension on their nature. In this regard, it is necessary to deepen their knowledge under different engine technologies, operating conditions, fuel properties and after-treatment devices and how their measure is affected by the sampling and dilution procedure. This paper provides a study on the sub-23 nm particles emitted from a small direct/port fuel injection, spark ignition engine fueled with gasoline, ethanol and a 30% v/v ethanol/gasoline blend, at different operating conditions. Particles were measured both upstream and downstream of a three-way catalyst. The conditions of the sampling were changed in order to investigate the volatile organic fraction. For this purpose, the exhaust gas sample was diluted through a Particulate Measurement Programme compliant system. The temperature of the first dilution stage and of evaporation chamber were changed to discriminate the volatile compounds by enhancing the condensation and the nucleation processes. An engine Exhaust Particle Sizer was used for the sizing and the counting of the particles in the range 5.6–560 nm. The results show a strong dependence of the sub-23 nm particle emissions from the engine operating condition and the fuel type. A moderate impact of the three-way catalyst was instead observed. Moreover, a significant effect of the dilution parameters in the sampling system was noted pointing out the importance to define an appropriate protocol for the measurement of the sub-23 nm particles. Graphical abstract: Image 1 Highlights: Analysis of sub-23 nm particles from different injection systems and operating conditions was performed. Particles emitted by gasoline, ethanol and a 30 %v/v of ethanol blend were compared. Effect of sampling condition on sub-23 nm particles was studied. Volatile organic fraction of sub-23 nm particles emitted by a SI engine equipped with both PFI and DI systems was evaluated. The impact of a TWC on sub-23 nm particles was investigated.